General Route to Purin-2-ylmagnesium Halides by Metal–Halogen Exchange in Dichloromethane - Gazzola, Silvia; Gordon, Malcolm R.; Lindell, Stephen D. (Synlett, 2020)
Treatment of a solution of a 9-alkyl- or 9-aryl-2-iodopurine in dichloromethane with an ethereal solution of ethylmagnesium bromide at –5 °C generates the corresponding purin-2-ylmagnesium bromide, which reacts with aldehydes to give the corresponding 2-(hydroxyalkyl)purines in yields of 53–84%. The purin-2-yl Grignard reagents show good functional-group tolerance to ester and nitro groups, and the method permits the synthesis of the previously unknown 6-unsubstituted 2-magnesiopurines for the first time. Performing the same procedure in THF as solvent resulted either in extensive decomposition or rapid isomerization to give purin-8-ylmagnesium halides.
Keywords: nucleobases; purinylmagnesium halides; Grignard reaction; metal–halogen exchange; dichloromethane